Decoupling of nutrient cycles in a Eucalyptus woodland under elevated CO2. (25th June 2019) - Ochoa‐Hueso, Raúl; Piñeiro, Juan; Power, Sally A.
Abstract: Elevated atmospheric [CO2 ] (eCO2 ) is currently altering nutrient cycling and availability in ecosystems worldwide. If the availabilities and turnover rates of macro‐ and micronutrients are differentially affected, then nutrient cycles may become out of sync (i.e., decoupled). We evaluated the impacts of 3 years of eCO2 (550 µmol CO2 /mol) on the availability, stability and coupling of eleven essential macro and micronutrients in a mature, P‐limited Eucalyptus woodland from Eastern Australia (EucFACE). Despite increases in N and P availability in the first 18 months of study, nutrient availabilities and their stoichiometric ratios were unaffected by eCO2 across the study period (26–57 months of experimental duration). In contrast, the stability of nutrient availability increased under eCO2, which was concomitant with a reduction in the degree of biogeochemical coupling. Synthesis . We demonstrate that macro‐ and micro‐nutrient cycles can quickly become out of sync (i.e., decoupled) under eCO2 in a low‐nutrient Australian eucalypt woodland, despite the lack of consistent effects on nutrient availability; such decoupling of nutrient cycles may have unpredicted consequences in terms of ecosystem functioning under the widely assumed positive relationship between biogeochemical coupling and ecosystem functioning. Abstract : We demonstrate that macro‐ and micronutrient cycles can quickly become out of sync (i.e., decoupled) under eCO2 in a low‐nutrient Australian eucalypt woodland, despite the lack of consistent effects on nutrient availability; such decoupling of nutrient cycles may have unpredicted consequences in terms of ecosystem functioning under the widely assumed positive relationship between biogeochemical coupling and ecosystem functioning. RESUMEN: El aumento de las concentraciones de CO2 (eCO2 ) en la atmosfera está alterando el reciclado y disponibilidad de nutrientes en todo el mundo. Si las disponibilidades y tasas de reciclado de los distintos macro y micronutrientes se ven afectadas de forma diferencial, entonces los ciclos de nutrientes podrían desincronizarse (i.e., desacoplarse). Evaluamos el impacto de tres años de eCO2 (550 µmol CO2 mol ‐1 ) sobre la disponibilidad, estabilidad y acoplamiento de once macro y micronutrientes esenciales en un bosque maduro de eucaliptos del Este de Australia (EucFACE). Pese a un aumento en la disponibilidad de N y P en los primeros 18 meses de experimento, la disponibilidad de nutrientes y sus relaciones estequiométricas no se vieron afectadas por el eCO2 durante el periodo de este estudio (26 – 57 meses de duración experimental). Por el contrario, la estabilidad en la disponibilidad de nutrientes aumentó en condiciones de eCO2, lo que ocurrió de forma paralela a una reducción en el grado de acoplamiento biogeoquímico. Síntesis . Hemos demostrado cómo los ciclos de macro y micronutrientes pueden desincronizarse (i.e., desacoplarse) rápidamente en respuesta al eCO2 en un bosque de eucaliptos pobre en nutrientes de Australia; este desacoplamiento de los ciclos de nutrientes podría tener consecuencias impredecibles para el funcionamiento de los ecosistemas dada la ampliamente asumida relación positiva entre el acoplamiento biogeoquímico y el funcionamiento ecosistémico.